Analisis Hukum Positif dan Islam Crowdfunding Wakaf Yayasan SF di IslamPedia - Riyadh, Ahmad; Sulistiani, Siska Lis; Hayatudin, Amrullah (UNISBA Press, 2025)
Abstract. This study aims to analyze the compliance of the crowdfunding waqf system implemented by the Sinergi Foundation through the Islampedia Quran Belajar application, from the perspectives of positive law and Islamic law. The method used is a normative-juridical and descriptive-analytical approach, referring to Indonesian legislation and Islamic legal principles. The background of this research is the need for legal certainty and transparency in digital waqf practices. The results show that the system aligns with Law No. 41 of 2004, Government Regulation No. 42 of 2006, OJK Regulation No. 77/2016, and the Ministry of Social Affairs Regulation No. 8/2021. However, there remains a legal gap concerning the digital form of waqf contracts. From the Islamic legal perspective, the system meets the principles of caution (ḥiṭṭah), transparency, and contract validity in line with maqāṣid al-sharī‘ah, as well as the pillars and conditions of waqf. Crowdfunding waqf via Islampedia reflects Islamic philanthropic values and represents an acceptable innovation in contemporary waqf, although more specific technical regulations are still required to ensure stronger legal protection for the public Abstrak. Penelitian ini bertujuan menganalisis kesesuaian sistem crowdfunding wakaf yang dijalankan Yayasan Sinergi Foundation melalui aplikasi Islampedia Quran Belajar, ditinjau dari hukum positif dan hukum Islam. Metode yang digunakan adalah pendekatan normatif-yuridis dan deskriptif-analitis, dengan acuan pada peraturan perundang-undangan serta prinsip syariah. Latar belakang penelitian ini adalah pentingnya kepastian hukum dan transparansi dalam praktik wakaf digital. Hasil penelitian menunjukkan bahwa sistem ini telah sejalan dengan UU No. 41 Tahun 2004, PP No. 42 Tahun 2006, POJK No. 77/2016, dan Permensos No. 8/2021. Namun, masih terdapat kekosongan hukum terkait akad wakaf uang digital. Dalam perspektif hukum Islam, sistem ini memenuhi prinsip kehati-hatian (ḥiṭṭah), transparansi, serta keabsahan akad berdasarkan maqāṣid al-syarī’ah, rukun, dan syarat wakaf. Crowdfunding wakaf melalui Islampedia mencerminkan nilai filantropi Islam dan menjadi inovasi wakaf kontemporer yang dapat diterima secara hukum, meski tetap memerlukan regulasi teknis yang lebih spesifik.